Perception towards anaesthesia among the patients visiting a tertiary care centre in Kathmandu, Nepal - Raj Kunwar, Bhuban; Bhattarai, Niraj; Acharya, Puspa (Journal of Chitwan Medical College, 2025)
Introduction: The perception of anaesthesia as a 'behind-the-scenes' expertise has persisted, leading to a lack of public awareness regarding the role and responsibilities of anaesthesiologists. This study aimed to assess patients' knowledge and perceptions towards anaesthesia in a tertiary-level hospital. Method: The study was a cross-sectional design conducted in Shree Birendra Hospital, Kathmandu, involving 270 patients. Inpatients over 18 years old, scheduled for surgery requiring any anaesthesia, and those able to participate in a structured face-to-face interview were included, while those with severe health conditions were excluded. Data was collected in the pre-anaesthetic check-up (PAC) room between 5 Aug and 26 Oct 2024. A convenience sampling method was used for the sample selection. Ethical approval was obtained from the Institutional Review Committee (IRC) under Reg 1080, ensuring informed consent and participants' confidentiality were maintained. Descriptive analysis was performed using number percentage, central tendency measures. Result: The findings revealed that 137(50.7%) of patients were unaware of the purpose of anaesthesia, with 111(41.1%) rating their knowledge as poor. Despite previous anaesthesia experiences, significant fears persisted regarding potential risks such as death 170(63%) and waking up during surgery 167(61.9%). Most patients 215(79.6%) obtained information from healthcare workers and recognized the anaesthesiologist’s roles in various medical contexts; however, only 75(27.8%) viewed them as the chief in the operating room. Conclusion: The study underscores significant knowledge gaps about anaesthesia among patients, which contribute to anxiety and misconceptions